2006
DOI: 10.1186/1465-9921-7-85
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to ozone-induced airway inflammation is associated with decreased levels of surfactant protein D

Abstract: Background: Ozone (O 3 ), a common air pollutant, induces exacerbation of asthma and chronic obstructive pulmonary disease. Pulmonary surfactant protein (SP)-D modulates immune and inflammatory responses in the lung. We have shown previously that SP-D plays a protective role in a mouse model of allergic airway inflammation. Here we studied the role and regulation of SP-D in O 3 -induced inflammatory changes in the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 40 publications
4
78
0
1
Order By: Relevance
“…46 We have previously shown that the lung collectin SP-D has immunosuppressive activities 15 and that it protects against inflammatory changes of the lung. 40 In this study we investigated the regulatory link between these innate immune molecules. Our data demonstrate an early increase of TNF-α levels in response to allergen challenge in sensitized mice and late increases in SP-D associated with resolution of the inflammatory changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 We have previously shown that the lung collectin SP-D has immunosuppressive activities 15 and that it protects against inflammatory changes of the lung. 40 In this study we investigated the regulatory link between these innate immune molecules. Our data demonstrate an early increase of TNF-α levels in response to allergen challenge in sensitized mice and late increases in SP-D associated with resolution of the inflammatory changes.…”
Section: Discussionmentioning
confidence: 99%
“…For mouse SP-D ELISAs, we used an in-house anti-SP-D polyclonal antibody and protocol, as previously published. 40 Western blotting was performed as previously described. 41 …”
Section: Protein Assay Cytokine and Sp-d Elisa And Sp-d Western Blomentioning
confidence: 99%
“…It makes an important contribution to surfactant homeostasis and pulmonary immunity [5]. SP-D plays a role in: protecting against viral infection; clearance of bacteria, fungi and apoptotic cells; and resolution of inflammation [7]. Mice that lack SP-D develop chronic inflammation and emphysema that can be prevented by administration of truncated recombinant human SP-D [8].…”
mentioning
confidence: 99%
“…It was also reported that there is a protective effect of exogenous surfactant instillation to donor lungs before retrieval on post-lung transplantation surfactant function. 18 In addition, it was observed that absence or low levels of SP-D augment inflammation by acute oxidative stress in the mice model 19 and severe lung inflammation frequently occurred in SP-A-deficient mice receiving myeloablative allogeneic BM and spleen T-cells transplant. 11 Furthermore, in mice transtracheal human SP-A treatment attenuated the manifestation of IPS probably as a result of suppressed IFN-production by allo-activated lung-infiltrating T cells, and thereby, early survival was improved.…”
Section: Pretransplant Serum Sp-d As a Predictor For Bos/ipsmentioning
confidence: 99%